Guiding paving block porous for blind people - Isradi, Muhammad; Hidayat, Acep; Prasetijo, Joewono (Sciendo, 2020)
Porous concrete is a simple form of lightweight concrete made by eliminating the use of fine aggregates (sand). That is a mixture of cement, water and coarse aggregate. Use of the guiding paving block porous for blind people is one of the efforts that will be made to overcome the inundation due to water spills from sufficiently high rainfall, providing comfort and safety for users so as not to slip easily due to slippery road surfaces, that will be used must have a measurable value of permeability and porosity to optimize the function of using porous concrete. Guiding paving block porous for blind people are very economical and have a great advantage in absorbing water so the surface is always dry, and can reduce accidents due to slippery roads. Another advantage is that the product is environmentally friendly with handmade, designed using a mixture of plastic bottle waste material can be made apart from the manufacturing process in various shapes and various colors. From the test results it has a strength of 10-15 mpa in the precast age of 28 days with a water absorption capability of up to 10L / m2.